The traces of roman metallurgy in Eastern Serbia - Petković Sofija (Journal of Mining and Metallurgy. Section B: Metallurgy)
The archaeological traces of the Roman mining and metallurgy in eastern Serbia are rather frequent but insufficiently studied and published. Three mining-metallurgical regions abounding in gold, silver, copper, iron and lead could be distinguished there: 1. the upper course of the Pek river, metalla Pincensia, 2. the area between Bor, Zlot, Crna Reka and Rgotina and 3. the area in the river basin of Beli Timok, two latter ones had been organized as territoria metallorum. The archeometallurgical sites confirmed by investigations are: Kraku lu Jordan at the confluence of the Brodica river and the Pek river, Rudna Glava, Tilva Roš in Bor, Gamzigrad - Romuliana, Rgotina near Zaječar and Timacum Minus in the village Ravna near Knjaževac. Roman mining-metallurgical activities in eastern Serbia flourished from the end of the 3rd century, were interrupted by the invasion of Huns in AD 441. and restored in the time of emperors Anastasius and Justin I, in the end of the 5th - beginning of the 6th centuries. The Roman mining-metallurgical centers functioned in the 6th century until the Slav invasion in the beginning of the 7th century.